Succinate dehydrogenase (SDH)-deficient renal carcinoma: a morphologically distinct entity: a clinicopathologic series of 36 tumors from 27 patients - Gill, Anthony J; Hes, Ondřej; Papathomas, Thomas; Šedivcová, Monika; Tan, Puay Hoon; Agaimy, Abbas; Andresen, Per Arne; Kedziora, Andrew; Clarkson, Adele; Toon, Christopher W; Sioson, Loretta; Watson, Nicole; et al. (The American journal of surgical pathology, 2014)
Succinate dehydrogenase (SDH)-deficient renal carcinoma has been accepted as a provisional entity in the 2013 International Society of Urological Pathology Vancouver Classification. To further define its morphologic and clinical features, we studied a multi-institutional cohort of 36 SDH-deficient renal carcinomas from 27 patients, including 21 previously unreported cases. We estimate that 0.05% to 0.2% of all renal carcinomas are SDH deficient. Mean patient age at presentation was 37 years (range, 14 to 76 y), with a slight male predominance (M:F=1.7:1). Bilateral tumors were observed in 26% of patients. Thirty-four (94%) tumors demonstrated the previously reported morphology at least focally, which included: solid or focally cystic growth, uniform cytology with eosinophilic flocculent cytoplasm, intracytoplasmic vacuolations and inclusions, and round to oval low-grade nuclei. All 17 patients who underwent genetic testing for mutation in the SDH subunits demonstrated germline mutations (16 in SDHB and 1 in SDHC). Nine of 27 (33%) patients developed metastatic disease, 2 of them after prolonged follow-up (5.5 and 30 y). Seven of 10 patients (70%) with high-grade nuclei metastasized as did all 4 patients with coagulative necrosis. Two of 17 (12%) patients with low-grade nuclei metastasized, and both had unbiopsied contralateral tumors, which may have been the origin of the metastatic disease. In conclusion, SDH-deficient renal carcinoma is a rare and unique type of renal carcinoma, exhibiting stereotypical morphologic features in the great majority of cases and showing a strong relationship with SDH germline mutation. Although this tumor may undergo dedifferentiation and metastasize, sometimes after a prolonged delay, metastatic disease is rare in the absence of high-grade nuclear atypia or coagulative necrosis.
Keywords: Aged; polymerázová řetězová reakce; imunohistochemie; Succinate Dehydrogenase; Carcinoma, Renal Cell; lidé; lidé středního věku; senioři; ženské pohlaví; čipová analýza tkání; Tissue Array Analysis; mladiství; sukcinátdehydrogenasa; Adolescent; Female; mužské pohlaví; Polymerase Chain Reaction; Young Adult; Adult; karcinom z renálních buněk; mutační analýza DNA; Middle Aged; Kidney Neoplasms; Humans; dospělí; DNA Mutational Analysis; Male; nádory ledvin; mladý dospělý; Immunohistochemistry